Gender Feminism in the Thought of Christina Hoff Sommers. A Critique - Guczalska, Katarzyna (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
The goal of the article is to look critically at the thought of Christina Hoff Sommers, who, in her resounding book from 1995 Who Stole Feminism? How Women Have Betrayed Women, negatively evaluates the gender variant of feminism. According to Sommers, the left wing feminism betrayed the true matters of women and intensified hostility between women and men. Unfortunately, the libertarian feminism advocate’s disquisition is no deep and profound critique of the background of left-wing feministic movement but only a partial description of the environment of American radical feminists. Although authentic feminism should make use of theoretical findings of liberal traditions – Hoff Sommers doesn’t present any comprehensive analysis of the potential of libertarian thought in that matter.